Relation between Residents’ Attitudes and their Support for Tourism Development - Biju Gopal; Dr. Biju T. (International Journal of Psychosocial Rehabilitation, 2020)
Tourism industry has grown by unprecedented levels across the globe. It was initially considered as a solution to economic vagaries, providing local income and employment. Studies later revealed that tourism was not without ill-effects, and that uncontrolled tourism development can have strong implications on the sustainability of tourism destinations. Attitude of local community began to be considered as very important in deciding future development of tourism in destinations. The present study attempts to identify the local community residents’ community attachment, concern and ecocentric values and to identify its effect on their support for tourism development. A regression model was formulated and tested to find that residents’ community attachment and ecocentric values have positive effect, and community concern have negative effect on tourism development. The regression model was found to be statistically significant.